Propranolol decreases DRD3 and SLC1A2 gene expression in patients with essential tremor - Kandemir, Nefise; Gultekin, Murat; Kara, Mehmet; Bayram, Arslan; Tascioglu, Nazife; Mirza, Meral; Dundar, Munis (Faculty of Medicine, Trisakti University, 2020)
BackgroundEssential tremor (ET) is the most common disease among movement disorders. Genes such as essential tremor 1-4 (ETM 1-4), HS1-binding protein-3 (HS1BP3), dopamine receptor D3 (DRD3), leucine-rich repeat and Ig domain containing 1 (LINGO1), glial high affinity glutamate transporter member 2 (SLC1A2), FUS, high temperature requirement A2 (HTRA2) and TENM4 had been shown to be responsible for the genetic inheritance of the disease. The aim of the present study was to investigate the effect of propranolol on the expression of DRD3, SLC1A2, and HTRA2 genes in patients with ET.MethodsA study of non-randomized experimental design was conducted involving 76 subjects. They were divided into two groups: 38 patients with ET in the patient group (Group 1) and 38 healthy people in the control group (Group 2). DRD3, SLC1A2 and HTRA2 gene expressions were assessed before and after 8 weeks of propranolol treatment. Fahn-Tolosa-Marin tremor scale results were compared before and after propranolol administration. Kruskal Wallis test was used to determine differences in gene expressions between the groups.ResultsD3 dopamine receptor and SLC1A2 gene expression in the patient group appeared to be lower than in the control group (p<0.001). However, the HTRA2 gene expression level was significantly higher in the patient group (p<0.001). Conclusion D3 dopamine receptor and SLC1A2 gene expressions were decreased in ET patients which at first glance can be explained in relation to etiology, but after treatment it was not increased as expected but decreased even more.